Mass Spectrometry for Comprehensive Analysis of Metabolites - Neha Farid, Asma Bashir, Kashif Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Mass spectrometry is a highly sensitive high output instrumental analytical technique. It is used to determine the molecular mass but also gives the information on molecular structure and is used for quantification as well. It involves the measurement of mass to charge ratios of ions. It has become an essential tool in biological research and can be used to characterize a wide variety of biomolecules such as sugars, proteins, and oligonucleotides. Although it was developed 100 years ago, it continues to evolve both with respect to merit and applications in various fields of science and technology. Mass spectrometry is a field of studying macromolecules like proteins and complexes and has very high sensitivity also now compounds at the atom level can also be studied. In this present review, a brief history of mass spectrometry is discussed, and the basic principles of the technology are introduced. A summary of some current applications of mass spectrometry, current methods used to identify, quantify, and characterize proteins and peptides are then reviewed. The range of applications of mass spectrometry is considerable and only promises to grow as the technology continues to improve.